Apparent life-threatening event in infancy - Hee Joung Choi; Yeo Hyang Kim (Korean Pediatric Society, 2016)
An apparent life-threatening event (ALTE) is defined as the combination of clinical presentations such as apnea, marked change in skin and muscle tone, gagging, or choking. It is a frightening event, and it predominantly occurs during infancy at a mean age of 1-3 months. The causes of ALTE are categorized into problems that are: gastrointestinal (50%), neurological (30%), respiratory (20%), cardiovascular (5%), metabolic and endocrine (2%-5%), or others such as child abuse. Up to 50% of ALTEs are idiopathic, where the cause cannot be diagnosed. Infants with an ALTE are often asymptomatic at hospital and there is no standard workup protocol for ALTE. Therefore, a detailed initial history and physical examination are important to determine the extent of the medical evaluation and treatment. Regardless of the cause of an ALTE, all infants with an ALTE should require hospitalization and continuous cardiorespiratory monitoring and evaluation for at least 24 hours. The natural course of ALTEs has seemed benign, and the outcome is generally associated with the affected infants' underlying disease. In conclusion, systemic diagnostic evaluation and adequate treatment increases the survival and quality of life for most affected infants.